2019
DOI: 10.1186/s40360-019-0357-z
|View full text |Cite
|
Sign up to set email alerts
|

Novel coumarins active against Trypanosoma cruzi and toxicity assessment using the animal model Caenorhabditis elegans

Abstract: BackgroundChagas disease (CD) is a tropical parasitic disease. Although the number of people infected is very high, the only drugs available to treat CD, nifurtimox (Nfx) and benznidazole, are highly toxic, particularly in the chronic stage of the disease. Coumarins are a large class of compounds that display a wide range of interesting biological properties, such as antiparasitic. Hence, the aim of this work is to find a good antitrypanosomal drug with less toxicity. The use of simple organism models has beco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 48 publications
(53 reference statements)
0
4
0
Order By: Relevance
“…This approach is widely used in toxicological studies using the nematode Caenorhabditis elegans . [ 31,32 ]…”
Section: Resultsmentioning
confidence: 99%
“…This approach is widely used in toxicological studies using the nematode Caenorhabditis elegans . [ 31,32 ]…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it has been revealed that apigenin was effective against Leishmania tropica amastigote [ 66 ]. In addition, previous reports have shown that coumarins exhibit activity against the promastigote form of Leishmania major and Trypanosma cruzi [ 53 , 87 ]. Therefore, future studies on the anti- Toxoplasma activities of these compounds that were identified in M. chamomilla ( German chamomile ) flowers are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Considering this drug is effective in clearing T.cruzi as well in pre-clinical studies, an ongoing randomized, double-blind, placebo controlled trial is being carried out in Argentina, Bolivia and Spain to assess its efficacy in CD (NCT02498782). Interestingly, some natural compounds and dietary supplements such as microalgae extracts 147 , wasp venom 148 , coumarins 149 , South American Vernonieae 150 , curcumin 151 and Resveratrol 152 have been also studied for anti-tripanosomal activity, but more research is required This article is protected by copyright. All rights reserved to draw conclusions, and there is still close to no human clinical data.…”
Section: Pharmacological Treatment: New Treatment Strategies and Alternative Drugsmentioning
confidence: 99%
“…Interestingly, some natural compounds and dietary supplements such as microalgae extracts, 174 wasp venom, 175 coumarins, 176 South American Vernonieae, 177 curcumin 178 and Resveratrol 179 have been also studied for anti‐trypanosomal activity, but more research is required to draw conclusions, and there is still close to no human clinical data. The use of natural compounds to treat known diseases might lead to effective benefit–cost resources, considering that many of these compounds are not subject to patent restrictions and may be widely available.…”
Section: Nifurtimoxmentioning
confidence: 99%